Telescopic Overdenture as An Aesthetic Treatment for Partially Dentate Patients – A case report - M, Satrio Krestiono; Laksono, Harry (Indonesian Journal of Dental Medicine, 2018)
Background: Metal frame denture design is common used for partially dentate patient, one of the problem was a metal appearance from wrought wire or a metal casting clasp as retainer, which is not really aesthetic. Telescopic overdenture with its double crown will be the best solution for those cases. Purpose: The purpose of this case report was to reported telescopic overdenture design and fabrication where the aesthetic was the main consideration. Case: Sixty years old female patient, a businesswoman, came to Dental Hospital of Universitas Airlangga, complained about her upper partially dentate and 6 years lower fixed partial denture, which is not comfortable to wear and her upper anterior teeth doesn't look quite good. She wanted to make crowns and removable denture. Case management: After the diagnosis were made, the pretreatment plan were remove crown for the upper jaw, remove the bridges on lower jaw, and transitional dentures were made to maintain the VDO. The crowns and veneer were fabricated and inserted while the inner copings were tried up on prepared teeth. After the the dentures were produced, the inner copings were luted to the abutment teeth, and then the dentures were inserted using FGP (Friction GriP) cement for the friction effect. Discussion: Telescopic overdenture is consists of a double crown system known as "the telescopic”, the procedure involves fitting the remaining natural teeth with inner metal crowns, followed by outer crowns as part of an over denture that can be removed by the patient. Conclusion: This technique ensures that telescopic overdentures give natural aesthetic result.